2016
DOI: 10.1093/cid/ciw391
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Cohort to Investigate the Effects of Early Life Giardiasis on Growth and All Cause Diarrhea

Abstract: This prospective longitudinal birth cohort demonstrated that asymptomatic giardiasis in the first 6 months of life is a risk factor for poor linear growth. Furthermore, asymptomatic giardiasis neither increases nor decreases odds of having an all cause acute diarrheal episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 36 publications
(39 reference statements)
5
70
1
3
Order By: Relevance
“…Yet in the past several years, it has become apparent that Giardia infections that occur early in childhood (earlier than age 2) are associated with reduced height and weight attainment [17, 115], with a critical window of preventing infection between birth and 6 months of life having the greatest impact on growth faltering [115]. This window may be critical due to the establishment and shaping of the composition of intestinal microbiota that provide essential amino acids and vitamins used for growth [116].…”
Section: Immunopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Yet in the past several years, it has become apparent that Giardia infections that occur early in childhood (earlier than age 2) are associated with reduced height and weight attainment [17, 115], with a critical window of preventing infection between birth and 6 months of life having the greatest impact on growth faltering [115]. This window may be critical due to the establishment and shaping of the composition of intestinal microbiota that provide essential amino acids and vitamins used for growth [116].…”
Section: Immunopathologymentioning
confidence: 99%
“…As such, these two recent studies suggest that the prevention of exposure to this parasite is more important in preventing long-term growth deficiencies rather than early intervention therapies, such as the use of metronidazole [117]. Moreover, the cause for the variation in studies examining the association between Giardia and growth development may be due to the presence (or absence) of very early childhood Giardia infections since acquired childhood protection may only limit the severity of giardiasis rather than provide full protection [115]. …”
Section: Immunopathologymentioning
confidence: 99%
“…The Etiology, Risk Factors, and Interactions of Enteric Infections and Malnutrition and the Consequences for Child Health and Development (MAL-ED) study found an association with subclinical, non-diarrheal giardiasis and decreases in growth of children [16]. There are few studies attributing gut microbiome changes to giardiasis [17][18][19] and no published studies showing the impact on the human intestinal microbiome using multi-parallel real-time quantitative (qPCR) to detect the presence of Giardia and quantitating the burden of infection [20]. To date, most studies examining intestinal parasitism have not been able to study intestinal worms and protozoans simultaneously and to successfully dissect the relative contribution of each of the significant intestinal helminth or protozoan pathogens to specific diseases.…”
mentioning
confidence: 99%
“…8 Similarly, persistent Giardia detection in the first 6 months of life has been associated with malabsorption 9 and reduced linear growth in two studies. 9,56 Cryptosporidium parvum excretion has also been associated with growth faltering, although it is unclear if this association is driven by prolonged excretion after a symptomatic infection. 57 These data suggest that a primary mechanism for the pathogenesis of EE may involve exposure to pathogens through poor hygiene practices and contaminated food and water resulting in enteric infections.…”
Section: Current Definitionsmentioning
confidence: 99%